Selection of papers presented at the Symposium 'Semiconductor Lasers: Physics and Technology' : Effect of Cd content in barriers on the threshold energy of Auger recombination in waveguide structures with HgTe/CdxHg1-xTe quantum wells, emitting at a wavelength of 18 μm. (17th June 2019) - Fadeev, M A; Dubinov, A A; Aleshkin, V Ya; Rumyantsev, V V; Utochkin, V V; Gavrilenko, V I; Teppe, F; Hübers, H.-W.; Mikhailov, N N; Dvoretskii, S A; Morozov, S V
Abstract: The threshold energy of Auger recombination in HgTe/Cdx Hg1-x Te heterostructures with quantum wells (QWs) is analysed numerically for different compositions of the solid solution in barriers. It is demonstrated that the threshold energy depends nonmonotonically on the cadmium content in barriers and reaches a maximum at x ≈0.6–0.7. A comparison of the results of numerical calculations with experimental data on the temperature quenching of stimulated emission in a Cd0.1 Hg0.9 Te/Cd0.65 Hg0.35 Te structure gives grounds to expect a more than twofold increase in the quenching temperature of stimulated emission in structures with pure HgTe QWs and barriers with a high (≈0.6) cadmium content.